On Error Estimate of the Boundary Element Method for Parabolic Equations in a Time-Dependent Interval (Journal of Computational Mathematics, 2021)
This paper discusses the direct boundary element method for parabolic equations in a time-dependent interval. An optimal estimate of the error in maximum norm for the boundary element collocation scheme is given.